2009
DOI: 10.1111/j.1439-0531.2007.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbohydrates on the Ability of Bull Sperm to Bind to Bovine Oviduct Epithelial Cells

Abstract: In the present study, we investigated the effect of various carbohydrates on the ability of bovine spermatozoa to bind to the bovine oviduct epithelial cells (OECs). We also examined the fertilization competence and motility of spermatozoa that bind to OECs in the presence of carbohydrates. Frozen-thawed spermatozoa were incubated with OECs, with and without various carbohydrates. The sperms were then divided into two fractions: OEC-binding sperms (B-sperm) and non-OEC binding sperms (NB-sperm). The fertilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Furthermore, sperm-somatic cell interaction depends on the carbohydrate chains [23]. In addition, 5 mM GlcNAc increases sperm binding to oviduct cells in bovine [24]. Therefore, the contradictory results might be due to differences in oocyte state (COCs vs. denuded oocytes) and/or GlcNAc concentrations (50 vs. 5 mM).…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, sperm-somatic cell interaction depends on the carbohydrate chains [23]. In addition, 5 mM GlcNAc increases sperm binding to oviduct cells in bovine [24]. Therefore, the contradictory results might be due to differences in oocyte state (COCs vs. denuded oocytes) and/or GlcNAc concentrations (50 vs. 5 mM).…”
Section: Discussionmentioning
confidence: 81%
“…Spermatozoa incubated with OEC cultures showed higher penetration and monospermy rates when short time periods were used (Hunter 1981). Moreover, the fertilization and cleavage rates of spermatozoa unbound to oviductal cells culture were lower than those for spermatozoa attached to the OEC (Kon et al 2009). These results indicate that the ability of spermatozoa to bind to oviductal cells is related to their fertilizing ability.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the reservoir assembly, structural studies have pointed at the interaction between the rostral portion of the acrosome of the bull sperm and the OEC microvilli [3,36,54]. Several studies have suggested the participation of species-specific carbohydrate recognition in spermoviduct interaction [55][56][57], and specific proteins have been proposed to play a role in the formation of the oviduct sperm reservoir; among them are seminal plasma protein PCD-109 (BSP-A1/A2) [58,59], BSP-A3, and BSP-30-kDarelated proteins [60] in bovine spermatozoa. These proteins appear to be lost from the plasma membrane overlying the head during sperm capacitation, and this event is associated to a decrease in OEC-sperm binding [59,61,62].…”
Section: Discussionmentioning
confidence: 99%